IPDPS 2008. (Computer (00189162), 2008)
The article reports on the launch of the IEEE Computer Society's Technical Committee on Parallel Processing's (TCPP) PhD Forum. The Forum is a part of the Technical Committee's flagship conference, the International Parallel & Distributed Processing Symposium and was created to help students establish contacts in the job market while also enabling industry and academia representatives access to developing technologies in parallel and distributed computing. Students have to write an extended synopsis of their thesis work, the best submissions being brought to the conference at the expense of the TCPP.